Schizophrenia Like Psychosis in Patients with Epilepsy Case Report - Ranjan, Sanjeev; Chalise, Pratikshya; Pandey, Pradeep; Poudel, Reet; Aich, TK (Journal of Universal College of Medical Sciences, 2013)
Epilepsy and schizophrenia are both due to altered cerebral functioning and their history is often connected. Here we present a case of epilepsy of generalized tonic clonic type presenting with schizophrenia like symptoms. DOI: http://dx.doi.org/10.3126/jucms.v1i2.8408 Journal of Universal College of Medical Sciences Vol.1(2) 2013: 35-36